2017
DOI: 10.1016/j.bbadis.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 22 (HSPB8) reduces the migration of hepatocellular carcinoma cells through the suppression of the phosphoinositide 3-kinase (PI3K)/AKT pathway

Abstract: Small heat shock proteins (HSPs) regulate a variety of cell functions. Among them, HSP22 and HSP20 are recognized to be ubiquitously expressed in various tissues. With regard to hepatocellular carcinoma (HCC) cells, we previously reported that phosphorylated HSP20 plays a suppressive role in transforming growth factor (TGF)-α-induced cell migration and invasion. In the present study, we investigated whether or not HSP22 is implicated in HCC cell migration. We detected HSP22 protein expression both in human HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…This study group recently demonstrated that TGF-α induced the migration of HuH7 cells via the SAPK/JNK (18) and AKT (19) pathways. Therefore, the present study examined whether or not the ERK, p38 MAPK and Rho kinase pathways were also involved in the TGF-α-induced HuH7 cell migration.…”
Section: Effects Of Pd98059 Sb203580 or Y27632 On Tgf-α-induced Migrmentioning
confidence: 98%
See 2 more Smart Citations
“…This study group recently demonstrated that TGF-α induced the migration of HuH7 cells via the SAPK/JNK (18) and AKT (19) pathways. Therefore, the present study examined whether or not the ERK, p38 MAPK and Rho kinase pathways were also involved in the TGF-α-induced HuH7 cell migration.…”
Section: Effects Of Pd98059 Sb203580 or Y27632 On Tgf-α-induced Migrmentioning
confidence: 98%
“…A Transwell cell migration assay was performed using a Boyden chamber (polycarbonate membrane with 8 µm pores, Transwell; Costar; Corning, Inc.) as described previously (18,19). Briefly, the cultured cells were seeded (1x10 5 cells/well) onto the upper chamber in serum-free RPMI-1640 medium.…”
Section: Cell Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that HSP22 is expressed in human ovarian cancer cells, and enhances the transforming growth factor (TGF)‐α‐induced cell migration . In our recent study , we have shown that HSP22 directly interact with phosphoinositide 3‐kinase (PI3K) in human hepatocellular carcinoma cells, and regulate the cell proliferation and the migration. However, the precise role of HSP22 remains to be clarified.…”
mentioning
confidence: 99%
“…We have previously demonstrated that HSP22 is expressed in human ovarian cancer cells, and enhances the transforming growth factor (TGF)-a-induced cell migration [14]. In our recent study [15], we have shown that Abbreviations HSPs, heat shock proteins; IL, interleukin; MAPK, mitogen-activated protein kinase; PI3K, phosphoinositide 3-kinase; TGF, transforming growth factor. HSP22 directly interact with phosphoinositide 3-kinase (PI3K) in human hepatocellular carcinoma cells, and regulate the cell proliferation and the migration.…”
mentioning
confidence: 99%